2005
DOI: 10.1007/s10529-005-3681-x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Detection in DNA Oligonucleotides Based on a Guanine Quenching Method Coupled with Enzymatic Digestion of Single-Stranded DNA

Abstract: Fluorescence quenching by guanine allows DNA hybridization to be monitored and any point mutations in oligonucleotides to be detected. However, fluorescence quenching is often affected by untargeted guanine located in a protruding end (single-strand DNA) of the probe-target DNA duplex resulting in an unsatisfactory sensitivity. In the present study, we used enzymatic digestion of the protruding end of a probetarget DNA duplex to avoid interference by untargeted guanine on fluorescence quenching for detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In this experiment, the fluorescence intensity decreased upon increases in the peptide concentration (Figure 6A); however, the percent change in the observed fluorescence intensity was fairly small (7%). One possible reason for this observation is quenching of the fluorescein fluorescence by the adjacent 5′-guanosine residue [63,64]. A plot of the fraction bound versus peptide concentration and hyperbolic curve fitting gave an apparent K D of 27 ± 4 μM (R 2 = 0.97) (Figure 6B ) .…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment, the fluorescence intensity decreased upon increases in the peptide concentration (Figure 6A); however, the percent change in the observed fluorescence intensity was fairly small (7%). One possible reason for this observation is quenching of the fluorescein fluorescence by the adjacent 5′-guanosine residue [63,64]. A plot of the fraction bound versus peptide concentration and hyperbolic curve fitting gave an apparent K D of 27 ± 4 μM (R 2 = 0.97) (Figure 6B ) .…”
Section: Resultsmentioning
confidence: 99%
“…This is probably because the quenching of ROX by the guanine base present in cGene-ROX is static and originates a non-emissive exciplex, whereas the exciplex of ROX with the other bases have higher fluorescence lifetimes. [18][19][20][21][22][23][24] After the addition of Gene-MG to cGene-ROX (in 180 mm buffer at 40 8C), the fluorescence decay curves become faster ( Figure 6), with the average lifetimes decreasing from 5.1 ns (before addition) to 4.2 ns after hybridization for all acceptor concentrations. This corresponds to an energy transfer efficiency [Eq.…”
Section: Fret Detection Of Dna Hybridization In Solutionmentioning
confidence: 99%
“…We note that the decays obtained for ROX-labeled DNA strands containing guanine could only be fitted by a sum of exponential functions because guanine is a ROX fluorescence quencher. [18][19][20][21][22][23][24] Previous results shown that the polarity of the PNIPAM shell [probed by fluorescence using dT25-Rox ( Figure 1)] is practically identical to the polarity of water at temperatures below the T VPT , but decreases sharply above T VPT because the shell dehy-drates. [25] The variation in shell properties strongly influences the distribution and dynamics of DNA adsorbed onto the shell of the nanoparticles at a temperature below T VPT .…”
Section: Introductionmentioning
confidence: 99%
“…The TBA has a random-coil structure in the absence of Pb 2+ . Because the internally labeled TMR can intramolecularly interact with the adjacent guanine bases by photo-induced electron transfer (PET) mechanism due to its good electron donating property [67][68][69][70][71], the rotation of TMR is firmly restricted, which results in the aptamer probe having large FA value. In the presence of Pb 2+ , because Pb 2+ can interact with aptamer probe and induce conformational change from a random-coil structure into a highly-ordered G-quadruplex [65,72], this would weaken or eliminate the intramolecular interaction between the TMR and the adjacent guanine bases involved in formation of the G-quadruplex.…”
Section: Principle Of Sensing Pb 2+ By Famentioning
confidence: 99%